1093. Infectious Complications after Pancreatic Islet Transplantation. (31st December 2020) - Raval, Milan; Lam, Anna; Cervera, Carols; Senior, Peter; Shapiro, James; Kabbani, Dima
Abstract: Background: Despite the significant advancement in islet transplantation over the past three decades, our understanding of infectious complications post islet transplant remains limited. Methods: This is a single center retrospective review of Islet transplant recipients at the University of Alberta between February 2006 and December 2015. All infectious episodes events occurring after transplant were categorized as opportunistic and non-opportunistic. Results: We analyzed 142 patients receiving a median of 2 islet transplants per patient, with 18 patients receiving 1 transplant (13%), 77 (54%) 2, 33 (23%) 3, 13 (9%) 4 and 1(1%) 5 transplants. Median age at first transplant was 50 years and 85 (47%) were male. Lymphocyte depleting agent with thymoglobulin or alemtuzumab was used for induction in 94% in first and 53% in second transplant. CMV serostatus was CMV D+/R- 61 (43%), CMVD+/R+ 52 (37%), CMVD-/R+ 16 (11%) and CMVD-/R- 13 (9%). CMV infection occurred in 21 patients (15%) [CMVD+/R- 6 (9.8%) and CMVR+ 15 (22.1%), p=0.06]. Other opportunistic infections included VZV 7 (4.9%), Nocardia 3(2.1%), and Pneumocystis jirovecii pneumonia 1. Non-opportunistic infections included skin and soft tissue infection 14 (9.9%), urinary tract infection 11 (7.7%), pneumonia 7 (4.9%) clostridium difficile infection (CDI) 4 (2.8%), and non-CDI gastroenteritis 5 (3.5%) (Table 1). Table 1: Infectious Complication post islet transplant Conclusion: Although the rate of infections after islet cell transplant is less frequent than other types of transplants, opportunistic infections, especially CMV, are not uncommon and should be considered in this setting. Disclosures: Carols Cervera, MD, PHD, Merk (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member, Other Financial or Material Support, Lecture fees) James Shapiro, MD, PHD FRCS(Eng) FRCSC MSM FRSC, ViaCyte (Consultant) Dima Kabbani, MD, Merck (Research Grant or Support)